Factors Affecting Repurchase Intention on Netflix Video on Demand Subscribers - Maria Paskahlina AR (Journal of Social Research, 2023)
This study aims to analyze the factors that influence repurchase intention in Netflix video-on-demand subscribers. The data used in this study is primary data taken from the results of filling out questionnaires of research respondents distributed by researchers online through online survey media platforms. The research sample was selected using the purposive sampling method so that a sample of 270 respondents was obtained. The data processing technique used in this study is using SEM which is assisted by using lisrel as software from the structural equation model. The results showed that eWOM affects the brand image, brand trust, and brand engagement. Furthermore, the results of this study also show that brand image, brand trust, and brand engagement can affect repurchase intention. This research is expected to be an input in increasing a good brand for video-on-demand users. In addition, it is also expected to continue to provide what consumers need so that what consumers expect can be fulfilled which in turn can increase consumer trust in Netflix. Video on demand managers are also expected to continue to engage through various ways, including through online media owned by the company so that this will also cause good eWOM for consumers so that new and old consumers will submit good comments on Netflix. This study has several limitations so it is expected that future researchers will conduct research on other video-on-demand users so that they have a larger number of respondents and are more accurate in their research results. In addition, further research is expected to examine other variables that can affect repurchase intention in video on demand users.